Persepsi Pengalaman Pengunjung Pameran terhadap Teknologi Self Service Registration - Romizal, Alba (Journal of Tourism and Creativity, 2023)
The increasing enthusiasm of visitors at exhibitions has had an impact that cannot be managed properly in the registration section. Thus making the professional exhibition organizer (PEO) as the event organizer present new innovations in managing visitor registration before entering the exhibition area. This innovation is self-service registration, by means of self-serving by the visitors themselves. That way it provides good two-sided benefits, namely for the PEO and the visitors who attend. Using a descriptive descriptive research approach with the method of observation, interviews, and literature study. Producing research findings that there is ease in the process of collecting visitor data and providing effectiveness for visitors to take advantage of their own gadgets. However, there are also problems when the server is down and when the internet connection is not connected, so that it has a direct impact on PEO to continue to be adaptive in developing this self-service innovation. Keyword: Events, Registration, Perception, Exhibition.